2017
DOI: 10.17221/668/2017-pse
|View full text |Cite
|
Sign up to set email alerts
|

Impact of poultry manure fertilization on chemical and biochemical properties of soils

Abstract: The aim of the research was to evaluate the chemical properties and enzymatic activity of arable soils which, for the period of 10 years, were fertilized with poultry manure (PM). Fertilization with PM resulted in a significant increase in the content of organic carbon and total exchangeable bases in soil. The application of that fertilizer increased the pH value. Fertilization with PM also slightly increased the total content of copper, manganese and iron. There was found, however, a significant increase in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 20 publications
2
5
0
Order By: Relevance
“…The result from the table showed that all treatments increased the exchangeable bases. This result correlates with the findings of Adeleye et al (2010), Ayeni and Ezeh (2017), Kobierski et al (2017), Dayo-Olagbende et al (2020), andAdekiya et al (2020) who stated that the application of amendments increases the exchangeable bases in the soil. The application of amendments significantly reduced the exchangeable acidity of the soil.…”
Section: Discussionsupporting
confidence: 91%
“…The result from the table showed that all treatments increased the exchangeable bases. This result correlates with the findings of Adeleye et al (2010), Ayeni and Ezeh (2017), Kobierski et al (2017), Dayo-Olagbende et al (2020), andAdekiya et al (2020) who stated that the application of amendments increases the exchangeable bases in the soil. The application of amendments significantly reduced the exchangeable acidity of the soil.…”
Section: Discussionsupporting
confidence: 91%
“…Organic amendments, such as CD and PM, serve to preserve soil fertility by acting as alternate sources of plant nutrients to chemical fertilizers, especially in rice production [15,16]. CD and PM improve the physical, chemical, and biological qualities of the soil, increasing nutrient availability [17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…The higher accumulation of trace metals in soil which increased with manure rate indicated potential soil pollution. Kobierski et al (2017) have also reported increased soil chemical properties in soil fertilized with poultry manure.…”
Section: Resultsmentioning
confidence: 91%
“…This is because livestock manure including poultry waste has been recognized as a source of heavy metal contaminant to agricultural soils while improving soil fertility (Hanč et al 2008;Luo et al 2009;Oguntade et al 2018). Hence, unconscious deposition of metal contaminants in soils through over fertilization with manure can increase heavy metal load of soil, contaminate food crops and endanger soil health and food chain (Khan et al 2017;Kobierski et al 2017).…”
Section: Introductionmentioning
confidence: 99%